A Note on the Volume of Soviet Investment - Nove, A. (The Review of Economics and Statistics, 1954)
THE purpose of this paper is to consider the probable increase in the volume of Soviet investment since I940, while subjecting to critical analysis such official figures as exist, as well as the attempts made outside Russia to throw light on this problem-the calculations of the Economic Commission for Europe 1 and of Dr. Naum Jasny.2 It goes without saying that the most we can expect from calculations of this kind is rough orders of magnitude. Apart from the many statistical doubts and uncertainties which we will encounter, investment covers a great variety of activities (from the Volga-Don canal to central heating installations, from turbo-generators to tractors), and both volume and price indexes naturally depend in part on the base-year weights chosen. However, we do know that the bulk of investment expenditure over 6o per cent in I940 8 and in the plan for I946-50 4 went for construction and installation. While it is true that there may have been relative shifts in the costs of different kinds of construction, which would affect the indexes to some extent, there is no reason to suppose that there was any substantial change in the dominant share of construction in total investment expenditure. Before tackling the question in detail, it is important to be clear about the meaning of the term investment. It is used to render the Russian words kapitalnye vlozhenia,5 which in principle means gross investment in fixed capital.6 Investment may be financed in the following ways: (a) by allocations from the state budget; (b) from resources (e.g., profits or a portion of the amortization fund) accumulated by state enterprises in the course of their operations; (c) from accumulations made outside the state-owned sector, above all by the collective farms (kolkhozy); (d) by loans granted by state credit institutions to, for instance, the kolkhozy, or to individuals (e.g., for housebuilding). Year by year, the Minister of Finance (Zverev) in his budget speech gives a figure to represent investment in the national economy, that is, covering items (a) and (b) of the above list. Unfortunately, it is not always clear just exactly what is included. In some years (consistently since I950, occasionally before that date) he specifically included in his investment figure the growth in the stocks of building organizations.7 Down to I946 inclusive, he made a distinction between centralized and investments (the former were centrally planned, the latter were smaller-scale investment projects in the state sector of the economy). After I 947 the figures he gave related to investment without any adjective, and the evidence suggests that those included decentralized investment from I949, or possibly from I948. (In I95I the category of